PENGEMBANGAN LEMBAR KERJA SISWA MATEMATIKA BERBASIS MASALAH UNTUK KELAS VIII SMP MATERI KUBUS DAN BALOK - Juariyah, Siti (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2016)
This study aims to generate math worksheets based on a valid and practical issues on the material cubes and blocks. This type of research was development of research (Research and Development), which consists of three stages of development of the definition (Define), the design (Design) and development (Develop). The subjects were students of class VIII SMPN 3 Ujung Batu in the first semester of the school year 2015/2016. The instrument used in this study was validation questionnaire sheet and questionnaire sheet practicalities. Based on test validity problem based worksheets that have been made to four people validator with some revisions and corrections then obtained an average score of problem-based validation results LKS was 3.17 with a valid category. Based on the practicalities of the test by using a questionnaire, observation of the implementation of learning then obtained an average score of problem-based LKS practicalities result was 81% in the practical category. So it can be concluded that based LKS is valid and practical problems.